DEGREE OF ACIDITY AND PHYSICAL PROPERTIES OF LITTER FERMENTED BROILERS WITH DIFFERENT INOCULANTS - R. W., Gurusinga; Sriyani, N. L. P.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine the effect of fermentation with different inoculants, namely EM-4, Ragi, and Bio-Bali tani, on the degree of acidity (pH) and physical properties of broiler litter waste. The study used a completely randomized design (CRD) consisting of 4 treatments, namely, fermentation with no inoculant + 1% molasses (LP0), fermentation with EM4 (effective microorganism 4) 1% + 1% molasses (LP1), fermentation with yeast (Saccharomyces 98 cerevisiae) 1% + 1% molasses (LP2) and fermentation using Bio-balitani inoculant 1% + 1% molasses (LP3). Each treatment used 4 replicates. The variables observed were acidity (pH) and physical properties (density, water absorption and water solubility). The results showed the mean value of pH in LP1, LP2, LP3 of 5.08, 5.17 and 4.85 were statistically significantly different (P<0.05) lower than LP0. The average value of density in LP1, LP2 was 0.51g/ml, 0.52g/ml, LP1 was not significantly different (P>0.05) and LP2 was significantly different (P<0.05) higher than LP0, in LP3 the average value of density was 0.47g/ml lower and not significantly different (P>0.05) compared to LP0. The average water absorption rate in LP2 and LP3 of 151.98% and 147.22% was not significantly different (P>0.05) higher than LP0, in LP1 of 125.38% was not significantly different (P>0.05) lower than LP0. The average levels of water solubility of LP1, LP2 and LP3 were 62.00%, 62.45% and 62.50% higher and significantly different (P <0.05) from LP0. Based on the results of the study, it can be concluded that the use of various types of inoculants in the fermentation process of broiler litter can improve the quality of acidity (pH) and physical properties.